2016
DOI: 10.1016/j.cell.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Wiring and Molecular Features of Prefrontal Ensembles Representing Distinct Experiences

Abstract: SUMMARY A major challenge in understanding the cellular diversity of the brain has been linking activity during behavior with standard cellular typology. For example, it has not been possible to determine whether principal neurons in prefrontal cortex active during distinct experiences represent separable cell types, and it is not known whether these differentially active cells exert distinct causal influences on behavior. Here, we develop quantitative hydrogel-based technologies to connect activity in cells r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
328
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 308 publications
(355 citation statements)
references
References 55 publications
17
328
2
2
Order By: Relevance
“…While the role of glutamatergic inputs to the medial core of NAc in promoting reward seeking has been studied (Britt et al, 2012; Otis et al, 2017; Pascoli et al, 2014; Qi et al, 2016; Stuber et al, 2011), here, we demonstrate that glutamatergic inputs to lateral shell of NAc can encode and drive punishment or aversion responses. Furthermore, while previous work reported that cocaine-activated neurons in mPFC exhibit high levels of NPAS4 expression and project to medial shell of NAc (Ye et al, 2016), we here did not observe elevated expression of NPAS4 in mPFC neurons that project to lateral shell of NAc and drive aversion. Thus, not only do mPFC neurons projecting to lateral versus medial NAc exhibit key differences in behavioral effects but also are defined by distinct molecular signatures, which may be of both basic and translational significance.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…While the role of glutamatergic inputs to the medial core of NAc in promoting reward seeking has been studied (Britt et al, 2012; Otis et al, 2017; Pascoli et al, 2014; Qi et al, 2016; Stuber et al, 2011), here, we demonstrate that glutamatergic inputs to lateral shell of NAc can encode and drive punishment or aversion responses. Furthermore, while previous work reported that cocaine-activated neurons in mPFC exhibit high levels of NPAS4 expression and project to medial shell of NAc (Ye et al, 2016), we here did not observe elevated expression of NPAS4 in mPFC neurons that project to lateral shell of NAc and drive aversion. Thus, not only do mPFC neurons projecting to lateral versus medial NAc exhibit key differences in behavioral effects but also are defined by distinct molecular signatures, which may be of both basic and translational significance.…”
Section: Discussioncontrasting
confidence: 80%
“…To perform unbiased molecular profiling of mPFC neurons projecting to NAc (mPFC → NAc) or to VTA (mPFC → VTA), we injected the retrograde canine adenovirus CAV2 encoding Cre recombinase (CAV2-Cre; Hnasko et al, 2006; Soudais et al, 2004) into either NAc or VTA of Cre-dependent ribosome-GFP-tagged transgenic mice (Long et al, 2014; Ye et al, 2016) and analyzed the mRNA bound to ribosomes using microarrays (Figure 1A). We found genes preferentially enriched (>1.5-fold) in either mPFC→NAc or mPFC→VTA projecting neurons (Figure 1B), 35 in mPFC→NAc and 16 in mPFC→VTA neurons (Tables 1 and S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In TRAP2;Ai14 double transgenic mice, neuronal activation results in the expression of CreER, which enters the nucleus in response to 4-hydroxytamoxifen (4-OHT) injection and causes recombination. This results in permanent expression of tdTomato (Cre reporter from Ai14 ) in active neurons (2426) (Fig. 1B).…”
mentioning
confidence: 99%
“…Dr. Gordon, a self-proclaimed circuit psychiatrist, emphasizes collaboration between clinicians working on humans and basic neuroscientists working on model systems in order to link genes, circuits, and behaviors [25], activities leading to new and more specific therapeutic approaches to psychiatric disorders. One good example of linking behaviors, circuits, and genes is recent work from the Deisseroth laboratory [26], in which after behavioral characterization, the authors identified connectomes of different cell populations in the medial prefrontal cortex of mice activated during a certain behavior in a brain-wide manner and characterized differences in gene expression patterns in these cells. As for leading to therapeutics, the fear circuitry, for example, has been studied extensively both in animal models and in humans [27,28,29] (Fig.…”
Section: Figmentioning
confidence: 99%